Analysis of unlawful acts regarding claims and the unlawful installation of confiscation sign (study of decision number 966/Pdt.G/2024/PN Medan) - Sitompul, October Yohanes; Siregar, Fitri Yanni Dewi (Priviet Social Sciences Journal, 2025)
This study aims to analyze unlawful acts in claims and the unauthorized installation of Sita signs. This study focuses on Decision No. 966/Pdt. G/2024/PN Medan, which involves a dispute between the Plaintiff and the Defendant regarding land rights. In this case, the Defendant installed a sita sign without permission from the Plaintiff, resulting in loss and a violation of ownership rights. To address this issue, references are made to agrarian law theories and relevant regulations. Data were collected through interviews with landowners, lawyers, and government officials, legal document analysis, and observations at the dispute location. The obtained data were analyzed qualitatively to understand the legal practices occurring, and the results of the study indicate that the defendant’s actions can be categorized as unlawful acts in accordance with Article 1365 of the Civil Code, which regulates liability for losses arising from unlawful acts.